Pengaruh Budaya dan Profesionalisme Pada Efektifitas Auditor Internal Pemerintah (Studi Pada Inspektorat di Madura) - Febrianto Dwi Saputro; Alexander Anggono (BAJ: Behavioral Accounting Journal, 2022)
This study is conducted to examine the impact of ‘ewuh pakewuh’, competence, ethics, and independence of auditor towards the effectiveness implementation of internal audit particularly in inspectorates located at Madura island. The research method employed in this study is a quantitative approach. Data used in this research is primary data by dissemination of questionaires to the inspectorates’ employee. Using purposive sampling to choose the sample and then using multiple linear regression to analyzed, sample of this study is fifty inspectorates’ employee and after data processing, the findings of this research signify that competence and independence significantly affect to the effectiveness of governmental internal audit, especially internal audit in inspectorate in Madura. Meanwhile, ‘ewuh pakewuh’ culture and ethics do not affect the effectiveness implementation of internal audit, especially in inspectoratein Madura. Furthermore, this study offers novelty from cultural perspective applied as analytical tools of statistical findings, i.e. Theory of attitude and behaviour, and the role theory.